Stand down: a journal of applied communication research forum on extremism and White nationalism in the United States military. Issue 5 (3rd September 2022) - McDermott, Victoria; May, Amy; Hernández, Leandra H.; Erdemandi, Max; Mararac, Nick; Bean, Hamilton; Howe, William T.; Braddock, Kurt; Munz, Stevie; Yamaguchi, Precious; DiCamillo, Alexa
ABSTRACT: The spread and acceptance of extremism and White nationalism throughout United States institutions poses some of today's most difficult challenges to national (in)security. This forum brings together scholars from a variety of backgrounds and perspectives to center communication in an effort to investigate, disrupt, and mitigate extremism and White nationalism within the United States military (USM). Ultimately, we challenge future scholars to continue this invaluable line of research so that we may continue to support the needs of a diverse combat force and mission success of the USM.